2020
DOI: 10.1371/journal.pone.0231173
|View full text |Cite
|
Sign up to set email alerts
|

Cell-permeable succinate prodrugs rescue mitochondrial respiration in cellular models of acute acetaminophen overdose

Abstract: Acetaminophen is one of the most common over-the-counter pain medications used worldwide and is considered safe at therapeutic dose. However, intentional and unintentional overdose accounts for up to 70% of acute liver failure cases in the western world. Extensive research has demonstrated that the induction of oxidative stress and mitochondrial dysfunction are central to the development of acetaminophen-induced liver injury. Despite the insight gained on the mechanism of acetaminophen toxicity, there still is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
(68 reference statements)
0
15
1
Order By: Relevance
“…Metformin and acetaminophen are widely used drugs which, similarly to statins, have been reported to inhibit the NADH-supported mitochondrial respiration and this unfavorable effect has been recently overcome by the use of cell-permeable succinate [ 19 , 20 ]. Similarly, the NADH-linked mitochondrial respiratory impairment caused by cerivastatin and atorvastatin in the present study was counteracted by means of a cell-permeable succinate prodrug, NV118 that bypassed the mitochondrial dysfunction and recovered the coupled (ATP-generating) respiration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metformin and acetaminophen are widely used drugs which, similarly to statins, have been reported to inhibit the NADH-supported mitochondrial respiration and this unfavorable effect has been recently overcome by the use of cell-permeable succinate [ 19 , 20 ]. Similarly, the NADH-linked mitochondrial respiratory impairment caused by cerivastatin and atorvastatin in the present study was counteracted by means of a cell-permeable succinate prodrug, NV118 that bypassed the mitochondrial dysfunction and recovered the coupled (ATP-generating) respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in isolated mitochondria in the LEAK state have shown that when supplied with saturating levels of succinate part of the electron flow is reversed and travels back through complex I generating reactive oxygen species (ROS) [ 56 ]. However, the risk of ROS increases through this mechanism seem to be low in the presence of complex I inhibition, which is exactly when cell-permeable succinates should be used [ 20 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell–permeable succinates have been successfully used to rescue mitochondrial respiration in experimental models of acute complex I inhibition [ 21 , 22 ]. We recently showed in acute experiments using human platelets and HepG2 cells that a cell–permeable succinate prodrug, NV118, can bypass complex I mitochondrial dysfunction induced by statins [ 23 ].…”
Section: Introductionmentioning
confidence: 99%